Intrinsic electrical properties of mammalian neurons and CNS function: a historical perspective - Llinás, Rodolfo R. (Frontiers in Cellular Neuroscience, 2014)
This brief review summarizes work done in mammalian neuroscience concerning the intrinsic electrophysiological properties of four neuronal types; Cerebellar Purkinje cells, inferior olivary cells, thalamic cells, and some cortical interneurons. It is a personal perspective addressing an interesting time in neuroscience when the reflex view of brain function, as the paradigm to understand global neuroscience, began to be modified towards one in which sensory input modulates rather than dictates brain function. The perspective of the paper is not a comprehensive description of the intrinsic electrical properties of all nerve cells but rather addresses a set of cell types that provide indicative examples of mechanisms that modulate brain function.